ARTIFICIAL INTELLIGENCE FOR METACOGNITIVE KNOWLEDGE ENHANCEMENT: EFL LEARNERS’ PERCEPTIONS IN AN INDONESIAN UNIVERSITY - Dira, Benito; Kuswandono, Paulus (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2024)
This study examines the understanding of English as a Foreign Language by master’s degree students about incorporating AI-driven applications into learning to boost their metacognitive knowledge at Driyarkara University (Pseudonym). The objectives explore the EFL learners’ understanding of digital applications for enhancing metacognition and their experiences utilizing the tools for enhancing metacognitive knowledge. Purposive-comprehensive sampling was utilized in mixed-method research. Twelve students from the first semester of the English Education Master Program (EEMP) were the research participants for the survey. Close-ended and open-ended responses were analyzed to discover the various impacts of AI-powered tools, such as Google Gemini and Chat GPT, which would be classified in the coding process. The unstructured interview transcripts were deciphered to detect EFL learners’ experiences using AI-powered tools to enhance metacognitive knowledge. The findings revealed that AI-powered tools could give learners insightful feedback, a personalized learning style, and more self-assessment opportunities. Enhancing metacognitive knowledge was needed to establish an effective way of thinking and construct critical thinking outcomes. This study also suggested that AI-powered tools provided EFL learners more flexibility to gather materials and search for further references.